STRATEGI PENGADOPSIAN TEKNOLOGI DALAM PEMBELAJARAN INTEGRATIF DAN KOLABORATIF PASCA-PANDEMI COVID-19 - Kanisius Supardi; Eliterius Sennen (Jurnal Literasi Pendidikan Dasar (JLPD), 2022)
This paper aims to examine strategies for using technology in integrative and collaborative learning after the Covid-19 pandemic by placing teachers as key actors. The scope of this research is limited to the Manggarai context as a field of analysis. This research is analytical-descriptive. The approach used is a qualitative approach with a constructivism paradigm. The data in this study were obtained from the results of literature studies and context analysis. The results of the study show that during the Covid-19 pandemic, distance learning models that rely on technological innovation are no longer an option as in previous times, but become an obligation. However, the integration of technology into distance learning is urgent. Many parties are not ready. Learning from this experience, the author recommends the need to develop a comprehensive technology adoption strategy in an integrative and collaborative learning model after the Covid-19 pandemic. This is important because post-Covid-19 pandemic we will face a “new normal” situation which is no longer the same as the situation before and during the Covid-19 pandemic. The developed strategy needs to place the teacher as a key actor because technology cannot completely replace the teacher’s role. In the context of the Manggarai community, the implementation of the strategy needs to take into account the social, economic, cultural, and geographical conditions of the community.